Eosinophilic gastroenteritis without identifiable allergens in an adult: A case report - Haisheng Lan; Tishang Yang; Li Zhou; Jiansheng Lv; Xvsen Huang (SAGE Open Medical Case Reports)
Eosinophilic gastrointestinal is an uncommon disorder affecting all tissues of the digestive tract. Eosinophilic gastroenteritis presents with a complex clinical profile, lacks specificity, and is prone to misdiagnosis in patients without evident allergens. In some instances, it is mistaken for an acute abdomen or a gastrointestinal tumor, potentially leading to unnecessary surgical interventions. We present the case of a 21-year-old female with eosinophilic gastroenteritis whose primary clinical manifestations were abdominal pain and ascites.